2005
DOI: 10.1111/j.1399-0012.2005.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Pneumocystis carinii pneumonia after stem cell transplantations a contagious disease?

Abstract: We report of twins who underwent hematopoietic stem cell transplantation (HSCT) for neonatal acute leukemia. Hospitalized in the same room from the time the first one demonstrated respiratory symptoms, they both developed Pneumocystis jiroveci (formerly carinii) pneumonia (PCP) 2 wk apart. This observation suggests that PCP may be a contagious disease in HSCT recipients. This may be especially true for infants and young children who are at risk of primary P. jiroveci infection, and should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Pneumocystis is a common microorganism identified approximately 100 years ago and categorized as a fungus depending on RNA sequence analysis [66]. The historical name Pneumocystis carinii has been currently modified as P. jirovecii.…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…Pneumocystis is a common microorganism identified approximately 100 years ago and categorized as a fungus depending on RNA sequence analysis [66]. The historical name Pneumocystis carinii has been currently modified as P. jirovecii.…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…Pneumocystis jiroveci has been reported to be a rare cause of pulmonary infection in HSC transplant recipients (Saito et al 2001;Chen et al 2003;Resnick et al 2005). The manifestations of disease depend on the severity of infection.…”
Section: Pneumocystis Jiroveci (Formerly Pneumocystis Carinii)mentioning
confidence: 99%
“…Abnormal chest radiographs have been reported in up to 90% of patients with suspected PCP showing the typical fi ndings of diffuse bilateral interstitial infi ltrates most marked in a perihilar distribution (Soubani et al 1996;Worthy et al 1997;Resnick et al 2005). As the disease progresses, alveolar infi ltrates may also develop.…”
Section: Pneumocystis Jiroveci (Formerly Pneumocystis Carinii)mentioning
confidence: 99%
“…Moreover, studies investigating the genotype of P. jiroveci in colonized patients have suggested that these patients play a role in the circulation and transmission of this micro-organism (Totet et al , 2004). Reports of outbreaks in hospitals among patients at risk (those with HIV, primary immune deficiencies, long-term immunosuppressive regimens, haematological and non-haematological malignancies, and/or severe malnutrition (Barbounis et al , 2005; Resnick et al , 2005; Hui & Kwok, 2006; Mori et al , 2009; Ritter & Pirofski, 2009) have strengthened this hypothesis (de Boer et al , 2011; Sassi et al , 2012). As the fungus cannot be cultured, in vitro experiments concerning transmission and epidemiology are difficult.…”
Section: Introductionmentioning
confidence: 99%